The microbiota of cork and yellow stain as a model for a new route for the synthesis of chlorophenols and chloroanisoles from the microbial degradation of suberin and/or lignin - Marina Ruiz-Muñoz; Ignacio Ontañón; Rebeca Cobos; Carla Calvo-Peña; Rebeca Otero-Suárez; Vicente Ferreira; Jordi Roselló; Juan José R. Coque (Microbiome)
Abstract Background The main application of cork is the production of stoppers for wine bottles. Cork sometimes contains 2,4,6-trichloroanisole, a compound that, at a concentration of ng/L, produces an unpleasant musty odor that destroys the organoleptic properties of wine and results in enormous economic losses for wineries and cork industries. Cork can exhibit a defect known as yellow stain, which is associated with high levels of 2,4,6-trichloroanisole. We describe how the microbiota of cork and yellow stain define a novel mechanism that explains the formation of chlorophenols and chloroanisoles (including 2,4,6-trichloroanisole) from p-hydroxybenzoate produced during lignin and/or suberin breakdown. Results Electron microscopy revealed that cork affected by yellow stain exhibited significant structural degradation. This deterioration was attributed to the presence of higher microbial populations compared to those found in standard cork. Cork microbiota is rich in filamentous fungi able to metabolize lignin. A metataxonomic analysis confirmed that yellow stain contained significantly greater populations of fungal species belonging to Absidia, Geomyces, Mortierella, Mucor, Penicillium, Pseudogymnoascus, Talaromyces, and Umbelopsis. It also contained significantly greater amounts of bacteria belonging to Enterobacterales, Streptosporangiales, Tepidisphaerales, Pseudomonas, and several members of Burkholderiaceae, particularly species of the Burkholderia-Caballeronia-Paraburkholderia group. The extraction of aromatic compounds from cork samples allowed the identification of several compounds typically observed following lignin depolymerization. Notably, p-hydroxybenzoic acid and phenol were detected. Two strains of the genus Streptomyces isolated from yellow stain were able to biotransform p-hydroxybenzoate into phenol in resting cell assays. Phenol could be efficiently chlorinated in vitro to produce 2,4,6-trichlorophenol by a fungal chloroperoxidase, an enzymatic activity commonly found in filamentous fungi isolated from cork. Finally, as has been widely demonstrated before, 2,4,6-trichlorophenol can be efficiently O-methylated to 2,4,6-trichloroanisole by many of fungi that inhabit cork. Conclusions Chlorophenols and chloroanisoles can be produced de novo in cork from p-hydroxybenzoate generated by the microbial biodegradation of lignin and/or suberin through the participation of different types of microorganisms present in cork. The natural origin of these compounds, which are of great interest for the chlorine cycle and represent a new source of environmental contamination that differs from that caused by human activity, is described. Video Abstract